Innovation and inspiration - Ash, Eve.; Quarry, Peter; Safari eBooks ([S.l.] : Seven Dimensions, 2014)
"It's great to be inspired to break new ground and create competitive advantage. These nine video chapters lead the way on developing visions and bringing ideas to a reality, having a beginner's mindset and being able to take risks. Leading thinkers and creators of great workplace cultures speak out and provide practical ideas to inspire innovation and new ways to work."--Resource description page.
Title from resource description page (viewed Apr. 8, 2014).
Presenter, Peter Quarry.
Keywords: Creative ability in business; Organizational change; Electronic books